2016
DOI: 10.1007/s00396-016-3906-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anionic polyacrylamide on stability and surface properties of the Al2O3–polymer solution system at different temperatures

Abstract: The stability mechanism and thermal properties of the system alumina–anionic polyacrylamide (PAM) was studied. The polymer’s adsorption properties in dependence on the following parameters solution pH (in the range 3–9), temperature (in the range 15–35 °C), and carboxyl groups’ content in the PAM chains (in the range 5–30 %) were examined. The turbidimetry method was applied for determination of the suspension stability of alumina in the presence of PAM. The obtained results indicate that the polymer addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…For both initial concentrations of cationic polyacrylamides, the adsorbed amounts are relatively high, which prevents flocculation. Flocculating ability of polyacrylamide at appropriate concentration was also confirmed by other researchers [42,43].…”
Section: C-sio2 Aggregation Without and With Ionic Polyacrylamide/cu(ii) Ions In The Simple And Mixed Systemssupporting
confidence: 73%
See 1 more Smart Citation
“…For both initial concentrations of cationic polyacrylamides, the adsorbed amounts are relatively high, which prevents flocculation. Flocculating ability of polyacrylamide at appropriate concentration was also confirmed by other researchers [42,43].…”
Section: C-sio2 Aggregation Without and With Ionic Polyacrylamide/cu(ii) Ions In The Simple And Mixed Systemssupporting
confidence: 73%
“…Wiśniewska et al also examined the impact of functional group content on the polyacrylamide adsorbed amount. This team used montmorillonite [42], alumina [43] and chromium(III) oxide [44] as adsorbents in the studies. It was found that on the montmorillonite surface polyacrylamide containing greater number of carboxylic groups was adsorbed in smaller quantity.…”
Section: C-sio2 Aggregation Without and With Ionic Polyacrylamide/cu(ii) Ions In The Simple And Mixed Systemsmentioning
confidence: 99%
“…A vertical scan analyzer measured the gravitational sedimentation under stagnant conditions. In this study (Figure a), the sedimentation efficiency for the suspensions was determined considering the TSI (Turbiscan stability index) factor as a function of time, where the higher the TSI, the lower the stability of the suspension (i.e., more efficient flocculation) would be achieved . Previous findings discussed the MW of the flocculants and their gravitational settling efficiency in aluminum oxide suspensions …”
Section: Resultsmentioning
confidence: 99%
“…In this study (Figure 9a), the sedimentation efficiency for the suspensions was determined considering the TSI (Turbiscan stability index) factor as a function of time, 112 where the higher the TSI, the lower the stability of the suspension (i.e., more efficient flocculation) would be achieved. 113 Previous findings discussed the MW of the flocculants and their gravitational settling efficiency in aluminum oxide suspensions. 111 In this shear-free test, the addition of TOL and starch showed no significant effect on the destabilization of aluminum oxide suspensions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The peak value is observed at 3 mgpol/gCaCO 3 when there is a high degree of bridging of CaCO 3 by the HPAM molecules. Beyond 3 mgpol/gCaCO 3 , we observed a clear display of the consequences of steric stabilisation due to overdosage of the polymer [26,27]. Above 3 mgpol/gCaCO 3 , the surface of the initially positively charged CaCO 3 particles would have been slowly saturated by the HPAM molecules and would have begun to impose repulsive force on one another and gradually weaken the effect of polymer bridging [13].…”
Section: Effect Of Polyacrylamide Molecular Weight On Calcium Carbona...mentioning
confidence: 88%